Pengukuran Jatidiri dan Daya Saing Koperasi dengan Pendekatan Development Ladder Assesment (DLA) Studi pada KUD Subur, KPRI Universitas Brawijaya, dan KWSU BAM di Kota Malang - Noor, Iswan (Universitas Brawijaya, Indonesia, 2015)
This research aims to test theoritically of the DLA variables in order to measure theidentity and competitiveness of cooperation. Development Ladder Assesment (DLA) approachapplied in order to decide cooperation identity category at KUD Subur, KPRI BrawijayaUniversity and KWSU BAM at Malang. Methods of analysis using DLA approach with variablevision, capacity, resources, and network, as well as DLA approach with Daniel Cotemodels and ICA ROAP Grid Model. KUD Subur is on the yellow zone means that KUD Suburin performance is generally satisfactory, however there are some indicators that need to beimproved for fixing the organization management. KPRI Brawijaya University and KWSUBAM are at the green zone, it means KPRI Brawijaya University and KWSU BAM performanceare good in terms of vision, capacity, and network resources. Daniel cote modelanalysis, KUD Subur, KPRI Brawijaya University and KWSU BAM in general are in quadrantI. These suggest that cooperatives have been better to implement their identity but stillweak in facing the intensity of the market (competition). Grid Model Analysis, KUD Subur,KPRI UB and KWSU BAM have occupied in quadrant I. It means that the three cooperativescategorize as cooperatives which have identity and able to perform the competition. KUDSubur has a good performance in applying the identity of cooperatives, but still low in doingthe competition. KPRI UB is good in the terms of performance in applying the identity ofcooperatives and fairly in conducting the competition. KWSU BAM applied a very goodperformance in applying the identity of cooperatives and doing well in the competition.